Designing Tunable DNA Condensates to Control Membrane Budding Transformation in Synthetic Cells - Nastasja Kaletta; Sophia Burick; Yusuf Qudbuddin; Petra Schwille (Advanced Science)
Abstract Wetting interactions between biomolecular condensates and lipid membranes have demonstrated great potential to induce large‐scale membrane transformations in synthetic cells. However, the ability to functionalize existing condensates and control their interactions with membranes is limited, restricting their utility in engineering controlled wetting behavior. Here, fully programmable condensates based on DNA Y‐motifs are introduced to engineer precisely tunable wetting behavior. In contrast to unmodified condensates that show no interaction with membranes, wetting of supported lipid bilayers (SLBs) can be induced by partial cholesterol‐functionalization of DNA nanostructures. Incorporating photoactivatable DNA‐lipid linker enables contact angles to be controlled over a wide range by varying UV exposure times. Furthermore, selective partitioning of small unilamellar vesicles (SUVs) into DNA condensates is demonstrated via programmable surface interactions. In giant unilamellar vesicles (GUVs), membrane wetting of enclosed condensates can be efficiently induced post‐fabrication and results in outward budding. Thus, this work establishes programmable DNA condensates as a powerful platform for fine‐tuned control over membrane‐associated processes in synthetic cells, exceeding traditional approaches such as altering lipid composition or environmental conditions. Finally, the platform provides the possibility to design smart drug carriers for controlled substance delivery and release, and represents a customizable model to study condensate‐membrane dynamics.